Experience in the application of bioactive dentin substitutefor direct pulp capping (LLC "Endo Press", 2020)
Effective treatment of pulpitis of teeth is an important and urgent problem of modern dentistry. The aim of the work was to evaluate the clinical effectiveness of the bioactive dentin substitute in the treatment of reversible forms of pulpitis. The doctors performed a procedure for direct coating of pulp in 87 teeth in 62 patients. . Most of the teeth in an objective study met all the criteria for success: the restoration was fully preserved (98.8% of the score was «good» and «excellent» according to the specified criteria), postoperative sensitivity was absent in the next (89.3%) and in the long term (95, 2%), the vitality of the teeth was confirmed with a cold test and radiologically (97.6% success).